(untitled) (Annals of Medical Research, 2021)
Aim: A blood gas analyzers (BGA) are vital equipment frequently used in emergency departments and intensive care units. It is clinically important that the measurements of a BGA and an autoanalyzer (AA) provide equivalent results, which is confirmed by their proximitiy to the absolute value. This study aimed to compare the sodium (Na+), potassium (K+), chloride (Cl-) and glucose values in venous blood samples measured with a BGA and a standard AA with external quality control values.Material and Methods: The results of patients that presented to our emergency department between April 1, 2019 and July 1, 2019 and underwent the measurements of Na+ (n = 5,908), K+ (n = 5,755), Cl- (n = 5,101) and glucose (n = 5,871) simultaneously by BGA and AA were retrospectively compared. Results: In the Spearman correlation analysis between the two measurements, the correlation coefficient (r) was found as 0.78, 0.88, 0.89 and 0.97 for Na+, K+, Cl- and glucose, respectively. According to the Bland-Altman analysis, in the comparison of Na+, K+, Cl- and glucose values, the average bias percentages at the 95% confidence interval were -0.8 (4.8 to -6.4), -9 (8.6 to -26.5), -0.2 (6.2 to -6.5), and 0.3 (21.8 to -21.3), respectively. Conclusion: We concluded that the Na+ and Cl- results obtained from BGA can be used instead of those obtained from an AA; however, the blood gas K+ and glucose results of the former cannot replace those of the latter.